2008
DOI: 10.1080/09585170801903266
|View full text |Cite
|
Sign up to set email alerts
|

Dread and passion: primary and secondary teachers' views on teaching the arts1

Abstract: This article reports on a study of the views of Scottish teachers concerning the delivery of arts subjects within the 5-14 curriculum. Data were gathered through focus group interviews with primary, secondary and primary head teachers, and a questionnaire survey of 232 teachers in 10 Scottish LEAs. Research issues included the balance of the curriculum; assessment; the specialist knowledge required to teach each subject with confidence; how the arts were valued by parents and schools; and the benefits which ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…However, this current study presents a more positive picture. Analysis of the questionnaire and interview data showed that, contrary to a number of studies (Chedzoy & Burden, 2007;MacLean, 2007;Wilson et al, 2008), dance currently forms part of the curriculum in a wide number of schools. The results indicated a significant increase in dance provision with 96% of schools including dance in the PE curriculum.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, this current study presents a more positive picture. Analysis of the questionnaire and interview data showed that, contrary to a number of studies (Chedzoy & Burden, 2007;MacLean, 2007;Wilson et al, 2008), dance currently forms part of the curriculum in a wide number of schools. The results indicated a significant increase in dance provision with 96% of schools including dance in the PE curriculum.…”
Section: Discussionmentioning
confidence: 85%
“…Teacher agency Wilson, MacDonald, Bryne, Ewing, and Sheridan (2008) and Connell (2009), when identifying some of the difficulties in planning, teaching and assessing dance, acknowledge that the practicalities for teaching dance are more demanding than that of other traditional activities. The planning and preparation that are involved in design and delivery of dance can act as a deterrent, which can result in teachers avoiding the activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence of increasing perceptions that specialist skills are required for teaching primary school subjects (e.g. Appleton, 2003;Goulding Rowland & Barber, 2002;Hennessy, 2000;Wilson et al, 2008). It is based on these discourses that the researchers purposed to find out the perceptions of primary school teachers to the existing generalist form of teaching to subject specialist teaching.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Much of the current research posits that specialist teachers bring a number of important dimensions to a subject. Hennessy, (2000) for example, argues that specialist teachers bring greater confidence to the classroom, while Wilson Macdonald, Byrne, Ewing, and Sheridan (2008) contend that subject specialists use their specialized content knowledge to empower students to produce a higher quality of work. Emotional and values-based claims have also been made about the use of specialist primary teachers.…”
Section: Literature Reviewmentioning
confidence: 99%